The strategic formulation of competitive advantage on private higher education institution using participatory prospective analysis. (2018) - Barusman, M. Yusuf Sulfarano
This study emphasises the participatory paradigm by using synthesis as a way of thinking in order to achieve its goal. The purposes of this study are to build future scenario of the external environmental dynamics that will be encountered by IPHEI, and to formulate a strategy that can be implemented by IPHEI through developing the organisation's competitive advantage in the future. The research methodology used is participatory prospective analysis (PPA). The results showed that the future scenario of external environmental conditions that will be encountered by IPHEI can be described in three conditions, namely: optimistic, moderate and pessimistic scenarios. The strategic formulation from the research results is based on four internal factors as its foundation (the effectiveness of leadership, the availability of funds and financing, the effectiveness of human resource management strategy, and the relevance of curriculum).